The house next door : thrillers - Patterson, James, 1947-; DiLallo, Susan, 1947-; DiLallo, Max; Arnold, Tim, (Journalist); Patterson, James, 1947-; Patterson, James, 1947-; Patterson, James, 1947- (New York : Grand Central Publishing, 2019)
Collects three stories, including "The Killer's Wife," in which Detective McGrath encourages a relationship with a suspect's wife in order to locate six missing girls.
The house next door / James Patterson with Susan DiLallo -- The killer's wife / James Patterson with Max DiLallo -- We. Are. Not. Alone. / James Patterson with Tim Arnold.
Keywords: Neighbors -- Fiction; Missing children -- Investigation -- Fiction; Witnesses -- Protection -- Fiction; Families -- Fiction; Missing persons -- Fiction; Human-alien encounters -- Fiction; Extraterrestrial beings -- Fiction; Thrillers (Fiction); Detective and mystery fiction